Parallels between phantom pain and tinnitus. (June 2016) - Peker, Selcuk; Sirin, Alperen
Abstract: Phantom pain and tinnitus are diseases that cause patients great discomfort. Both are phantom sensations that have many connections with cerebral structures, but their underlying mechanisms are not fully understood. Several therapies have been suggested for these conditions over the years, but there is still no consensus on how to treat either one. Comparison of these two phenomena reveals many similarities, including what is known about their underlying mechanisms, associated brain areas, and responses to therapeutic agents and methods. These similarities need to be evaluated in greater depth, as this could improve our understanding of tinnitus and phantom pain, and thereby improve management strategies for these conditions.